IMPORTANT QUESTIONS AND PROBLEMS OF GOLD MINING - Vorontsov, Y.N (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Consideration of issues and problems of gold mining makes instability in the economic, social and political relations of the population of our planet. For many centuries, gold has been the equivalent in determining solvency and is the most liquid asset. The problems of the development of gold mining have been debatable for more than a century. In the framework of gold mining, attention is drawn to various aspects of the interaction of gold mining enterprises with the external and internal operating environment, sustainability of development and economic security, an important role is played by competitiveness and security against threats from criminal structures and fraud in the variety of its manifestations. Leveling of various kinds of threats is possible only with a high level of financial stability and economic security of the gold mining enterprise, which characterizes the effectiveness of doing business in this area of activity. Providing financial stability and an effective system of economic security, gold mining enterprises are able to compete with leading analogues of the economic world. The competitiveness assessment toolkit is formed taking into account the potential of financial and economic activities of gold mining enterprises. Modern gold mining enterprises issues of sustainability of development, competition, economic, environmental, social security determine one priority plane, which determines their direct relationship and interdependence. Discussion of important issues and priority issues in terms of competitiveness, sustainability, economic, environmental, social security for gold mining enterprises is determined by the historical and current periods of development of society. The study of problematic issues helps to determine the long-term sustainable development of gold mining enterprises in the long-term temporary space.